Geochemistry of beach sands from the Bartın and Samsun-Ordu coastal districts, Northern Black Sea, Türkiye: implications for provenance - Halim Mutlu; Pelin Coşanay (Bulletin of the Mineral Research and Exploration)
This study aims to investigate geochemical and petrological characteristics, chemical weathering indices and provenance of the beach sands collected from 11 different sites along the coastlines of Bartın, Samsun and Ordu districts adjacent to mafic and intermediate volcanic rocks on the Pontides. Petrological findings show that the abundance of detrital quartz, feldspar and sedimentary lithic fragments increase in beach sands of the Bartın region where the SiO2 values fall in a wide range (47 to 87 wt.%). The Samsun and Ordu beach sands have moderately low SiO2 (50 to 61 wt. % and 48 to 62 wt. %, respectively) and relatively high Fe2O3 contents. LREE concentrations of investigated beach sands show enrichment patterns. Mafic minerals, especially pyroxene and magnetite grains are represented by eroded or abraded morphologies due to dissolution and erosion processes, while opaque heavy minerals show signs of recycling from basic adjacent rocks with etched to subrounded grain surface textures. The low chemical index of alteration (CIA) estimated for the beach sand samples implies the presence of fresh rock erosion along the coasts. We used magnetite to gain better understanding of the formation and origin of Fe-rich beach sands. The mineral chemistry data indicate that studied magnetites have quite similar composition and the mobility of trace elements exerts a great control on their distribution in magnetite.